Rapamycin for refractory discoid lupus erythematosus. Issue 5 (14th August 2018) - Herold, Mitchell; Richmond, Nicholas A.; Montuno, Michael A.; Wesson, Stanton K.; Motaparthi, Kiran
Abstract: Generalized discoid lupus erythematosus can pose a therapeutic challenge for dermatologists. Current treatment emphasizes photoprotection, topical and systemic steroids, and steroid‐sparing immunosuppressive agents if necessary. Rapamycin, also known as sirolimus, selectively inhibits mammalian target of rapamycin, a regulatory kinase responsible for multiple signal transduction pathways. Mammalian target of rapamycin inhibition reduces cell division, lymphocyte proliferation, cytokine release, and downstream pathways unique from other classes of immunomodulatory drugs. Herein, we present a case of generalized discoid lupus erythematosus resistant to topical steroids, prednisone, azathioprine, mycophenolate mofetil, hydroxychloroquine, and thalidomide. The addition of rapamycin led to a positive treatment response within 6 weeks, with good tolerance of the medication and no adverse effects. The current literature supporting the use of rapamycin in the treatment of autoimmune connective tissue diseases is also briefly reviewed. For patients with severe or generalized discoid lupus erythematosus refractory to conventional treatment, rapamycin may be a useful therapeutic consideration.